Efficacy and Safety of Tofacitinib Re-treatment for Ulcerative Colitis After Treatment Interruption: Results from the OCTAVE Clinical Trials. (21st April 2021) - Panés, Julian; Vermeire, Séverine; Dubinsky, Marla C; Loftus, Edward V; Lawendy, Nervin; Wang, Wenjin; Salese, Leonardo; Su, Chinyu; Modesto, Irene; Guo, Xiang; Colombel, Jean-Frederic
Abstract: Background and Aims: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis. Here, we evaluate the efficacy and safety of tofacitinib re-treatment following treatment interruption in patients with ulcerative colitis. Methods: Here, patients with clinical response to tofacitinib 10 mg b.d. induction therapy were randomised to receive placebo in OCTAVE Sustain. Those experiencing treatment failure after Week 8 of OCTAVE Sustain entered OCTAVE Open and re-initiated tofacitinib 10 mg b.d. [re-treatment subpopulation]; efficacy and safety data are presented up to Month 36 of OCTAVE Open. Results: Median time to treatment failure following interruption was 169 (95% confidence interval [CI], 94.0–179.0) and 123 [95% CI, 91.0–168.0] days for induction remitters, and induction responders but non-remitters, respectively. Following re-treatment with tofacitinib, rates (non-responder imputation after a patient discontinued; latest observation carried forward imputation after a patient advanced to a subsequent study [NRI-LOCF]) of clinical response, remission, and endoscopic improvement were 74.0%, 39.0%, and 55.0% at Month 2, and 48.5%, 37.4%, and 42.4% at Month 36, respectively. Among induction remitters and induction responders but non-remitters, clinical response rates at Month 36 were 60.6% and 42.4% [NRI-LOCF], respectively. Efficacy was recaptured regardless of prior tumour necrosis factor inhibitor failure status. The safety profile of tofacitinib 10 mg b.d. re-treatment was consistent with the overall cohort and demonstrated no new safety risks associated with exposure of ≤36 months. Conclusions: Median time to treatment failure was numerically higher in induction remitters versus induction responders but non-remitters. Following treatment interruption, efficacy was safely and successfully recaptured with tofacitinib 10 mg b.d. re-treatment in a substantial proportion of patients [ClinicalTrials.gov:NCT01458574;NCT01470612].